Three-dimensional hydrogel with human Wharton jelly-derived mesenchymal stem cells towards nucleus pulposus niche - Mohd Isa, Isma Liza; Zulkiflee, Izzat; Ogaili, Raed H.; Mohd Yusoff, Nurul Huda; Sahruddin, Natasya Nadia; Sapri, Shaiful Ridzwan; Mohd Ramli, Elvy Suhana; Fauzi, Mh Busra; Mokhtar, Sabarul Afian (Frontiers in Bioengineering and Biotechnology, 2023)
A regenerative strategy employing extracellular matrix (ECM)-based biomaterials and stem cells provide a better approach to mimicking the three-dimensional (3D) microenvironment of intervertebral disc for endogenous tissue regeneration. However, there is currently limited understanding regarding the human Wharton Jelly derived-mesenchymal stem cells (hWJ-MSCs) towards nucleus pulposus (NP)-like cells. Our study focused on the development of 3D bioengineered hydrogel based on the predominant ECM of native NP, including type II collagen (COLII) and hyaluronic acid (HA), which aims to tailor the needs of the microenvironment in NP. It was hypothesized that a hydrogel-based 3D fabricated from COLII enriched with HA mimics the NP niche in guiding WJ-MSC differentiation into NP-like cells by varying the biomacromolecule concentration in vitro. We successfully fabricated a 3D hydrogel using COLII 2 mg/ml and HA 10 mg/ml at a weight ratio of HA and COLII at 1:9 and 4.5:9, and both hydrogels physically maintained their 3D sphere-shaped structure after complete gelation. The higher composition of HA in the hydrogel system indicated a higher water intake capacity in the hydrogel with a higher amount of HA. All hydrogels showed over 60% hydrolytic stability over a month. The hydrogel showed an increase in degradation on day 14. The hWJ-MSCs encapsulated in hydrogel showed a round morphology shape that was 2 homogenously distributed within the hydrogel of both groups. The viability study indicated a higher cell growth of hWJ-MSCs encapsulated in all hydrogel groups until day 14. Overall, our findings demonstrate that HA/COLII hydrogel provides an optimal swelling capacity, stability, degradability, and non-cytotoxic, thus mimics the NP microenvironment in guiding hWJ-MSCs towards NP phenotype and potential uses as an advanced cell delivery system for intervertebral disc regeneration.